Determination of DUSP6 gene mutation and effect on craniofacial morphology among Malaysian Malay with class III malocclusion patients attending at Hospital Universiti Sains Malaysia - Nowrin, Shifat A (2016)
Class III malocclusion is a dominant inherited, slowly progressive dento-skeletal disharmony. It is characterized by over growth of mandible, stunted growth of maxilla, or a combination of both. The etiology of class III malocclusion and the role of genes in this phenotype remain indistinct. Recently, dual specificity protein phosphatases 6 (DUSP6) gene mutations have been reported to cause autosomal dominant form of class III malocclusion. The main objective of this study was to determine the DUSP6 gene mutation in three generations of Malaysian Malay subjects having class III malocclusion and to conduct their cephalometric analyses. Genetic analyses of DUSP6 gene were carried out in 30 subjects by selecting three individuals representing three generations, respectively, from ten Malaysian Malay families having Class III malocclusion and 30 healthy controls. Cephalometric radiographs were obtained only from class III malocclusion subjects and predetermined cephalometric linear and angular measurements were performed using Romexis software. t-test and analysis of variance (ANOVA) were used to analyse the cephalometric measurements from both mutation and non-mutation groups of class III malocclusion subjects. In the current study, a heterozygous missense mutation c.1094C>T (p. Thr 365 Ile) was identified in DUSP6 gene in three members of one family with class III malocclusion, whereas no mutation was found in the control group. t-tests showed significant differences in angular measurements Co-Gn-B andSN-MP variables in mutation group compared to the non-mutation group. Moreover, ANOVA showed no significant differences for all variables except in yen angle of 1st vs 2nd generation. In conclusion, current study successfully identified a missense mutation in DUSP6 gene among one Malaysian Malay family affected by class III malocclusion and cephalometrically found mandible was more prognathic from cranial base in mutation group compared to non-mutation group. The outcome of this study broadened the mutation spectrum of class III malocclusion and the importance of DUSP6 gene in craniofacial morphology.